ASSOCIATION OF PSYCHOSOCIAL FACTORS WITH ANXIETY AND DEPRESSION IN PATIENTS FOLLOWING ACUTE MYOCARDIAL INFARCTION (International Journal of Physiotherapy, 2015)
Background: Anxiety and depression are proven independent predictors of mortality, disability, and reduced health related quality of life (HRQoL). Hence, this study was undertaken with aim to find the prevalence of anxiety and depression in patients following acute myocardial infarction (AMI) and to find out its association with various psychosocial factors.Methods: Stable patients admitted during 3 month period in Cardiology Intensive care unit of tertiary care Hospital with the diagnosis of acute myocardial infarction were included in this cross sectional study. Data was collected using a Semi- structured questionnaire. Anxiety and depression were assessed using Hospital Anxiety and Depression Scale (HADS) .Scores were analyzed using SPSS version 16.Results: A total of 75 patients (73.3% men and 26.7% women) with mean age 54.86 ± 9.91 years were included. Mean scores of anxiety and depression were 4.49 and 4.0 out of 21, respectively. Probable cases of anxiety and depression as per HADS were 29.33% and 21.33% respectively. There was a statistically significant association of Anxiety and depression with gender (P= 0.004(A), P= 0.002(D); education [P=0.018(A), P= 0.002 (D)]; and pre-existing known stressor [P=